Social Constructivism, Mental Models, and Problems of Obedience - Werhane, Patricia Hogue 1935-; Hartman, Laura P.; Moberg, Dennis; Englehardt, Elaine; Pritchard, Michael; Parmar, Bidhan (2011)
There are important synergies for the next generation of ethical leaders based on the alignment of modified or adjusted mental models. This entails a synergistic application of moral imagination through collaborative input and critique, rather than “me too” obedience. In this article, we will analyze the Milgram results using frameworks relating to mental models (Werhane et al., Profitable partnerships for poverty alleviation, 2009), as well as work by Moberg on “ethics blind spots” (Organizational Studies 27(3):413–428, 2006), and by Bazerman and Chugh on “bounded awareness” (Harvard Business Review, 2006; Mind & Society 6:1–18, 2007) Using these constructs to examine the Milgram experiment, we will argue that the ways in which the experiments are framed, the presence of an authority figure, the appeal to the authority of science, and the situation in which the naïve participant finds herself or himself, all create a bounded awareness, a narrow blind spot that encourages a climate for obedience, brackets out the opportunity to ask the moral question: “Am I hurting another fellow human being?” and may preclude the subject from utilizing moral imagination to opt out of the experiment. We will conclude that these forms of almost blind obedience to authority are correctable, but with difficulty. We will argue that linking the modification of mental models to an unbinding of awareness represents an important synergistic relationship and one that can build effectively on the lessons learned from our experience with moral imagination.
Keywords: Moral Imagination; “blind spots”; bounded awareness; mental models; Milgram experiments